THE FORMATION OF LEGAL UNDERSTANDING OF SMOKING IN ISLAMIC EDUCATION: A COMPARATIVE STUDY OF THE PERSPECTIVES OF GUS BAHA AND USTADZ ABDUL SOMAD - Satra, Alihan; Febianti, Aisyah; Zaharah, Rezi; Vidyasari, Vivid; Septiani, Eka Zahra (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2025)
This study aims to explore the formation of legal understanding regarding smoking within the framework of Islamic education by analyzing the perspectives of two prominent Indonesian scholars, Gus Baha and Ustadz Abdul Somad. The legal interpretation of smoking in Islam remains a subject of scholarly debate, influenced by differing approaches to religious texts and contextual considerations. This research employs a qualitative method using discourse analysis to examine the sermons and public lectures of both scholars as disseminated through various digital platforms. The findings reveal that Gus Baha adopts a contextual, tolerant, and wisdom-oriented approach, emphasizing the importance of understanding social realities in interpreting Islamic rulings. In contrast, Ustadz Abdul Somad tends to employ a more textual and classical fiqh-based perspective, delivering his views in a direct and assertive manner. These differing methods of da'wah significantly shape public perceptions and legal understandings of smoking within the Muslim community. The study concludes that tailoring da'wah strategies to audience characteristics is crucial for the effective transmission of Islamic legal concepts, thereby facilitating broader acceptance and application of religious rulings in contemporary social contexts. Penelitian ini bertujuan untuk mengeksplorasi pembentukan pemahaman hukum mengenai rokok dalam kerangka pendidikan Islam dengan menganalisis pandangan dua ulama terkemuka Indonesia, yaitu Gus Baha dan Ustadz Abdul Somad. Penafsiran hukum Islam terkait merokok masih menjadi perdebatan di kalangan ulama, yang dipengaruhi oleh perbedaan pendekatan terhadap teks-teks keagamaan serta pertimbangan konteks sosial. Penelitian ini menggunakan metode kualitatif dengan pendekatan analisis wacana terhadap ceramah dan dakwah kedua tokoh yang disebarkan melalui berbagai platform digital. Temuan menunjukkan bahwa Gus Baha cenderung menggunakan pendekatan yang kontekstual, toleran, dan penuh kebijaksanaan, dengan menekankan pentingnya memahami realitas sosial dalam menafsirkan hukum Islam. Sebaliknya, Ustadz Abdul Somad lebih menekankan pendekatan tekstual dan berlandaskan fiqh klasik, dengan penyampaian yang tegas dan langsung. Perbedaan metode dakwah ini berpengaruh signifikan terhadap cara masyarakat memahami dan merespons hukum merokok dalam Islam. Penelitian ini menyimpulkan bahwa strategi dakwah perlu disesuaikan dengan karakteristik audiens agar penyampaian konsep hukum Islam lebih efektif, serta dapat diterima dan diterapkan dengan lebih luas sesuai konteks sosial masa kini.